Design ALU Based online BIST for Multi word-width RAM’s (International Journal of Engineering and Computer Science, 2015)
Memory cores are usually the densest portion with the smallest feature size in system-on-chip (SOC) designs. The reliability of memory cores thus has heavy impact on the reliability of SOCs. Transparent test is one of useful technique for improving the reliability of memories during life time. Transparent BIST schemes for RAM modules assure the preservation of the memory contents during periodic testing Symmetric Transparent Built-in Self Test (BIST) schemes skip the signature prediction phase required in traditional transparent BIST. Achieving considerable reduction in test time. Previous works or symmetric transparent BIST schemes require that a separate BIST module is utilized for each RAM under test. This approach, giver the large number of memories available in current chips, increase the hardware overhead of the BIST circuitry. In this work we propose a Symmetric transparent BIST scheme that can be utilized to test Rams. For 5 different word widths hence, more than one RAMs can be tested in a roving manner.